Association between cumulative incidence rates, mortality, and lethality from COVID-19 among the elderly and socioeconomic indicators - Tatiane Vitória Souza dos Reis; Priscila Poli; Sílvia Carla da Silva André Uehara (Universidade Federal do Ceará, 2024)
Objective: to analyze the association between the cumulative incidence, mortality, and lethality rates of COVID-19 in the older and socioeconomic indicators. Methods: this is an ecological time-trend study that considered all COVID-19 cases and deaths reported by the elderly people in all municipalities in the state of São Paulo. Results: weak positive correlations were found between the cumulative incidence rate of COVID-19 and factors such as the illiteracy rate in people aged 60 and over and elderly people with an income of up to one minimum wage. In addition, there were weak positive correlations between mortality and lethality rates and the municipal Human Development Index. There was a moderate correlation between the mortality rate and the rate of elderly people with no income. Conclusion: there is an association between income, schooling, and the municipal Human Development Index with the cumulative incidence, mortality, and lethality rates of COVID-19 in older people. Contributions to practice: the need for individualized and integrated approaches in health services is strengthened to minimize the effects of the social determinants of health on elderly people, especially in health emergencies.